(Diacetoxyiodo)benzene‐Mediated Oxygenation of Benzylic C(sp3)–H Bonds with N‐Hydroxyamides at Room Temperature. Issue 8 (5th February 2015) - Qian, Peng‐Cheng; Liu, Yu; Song, Ren‐Jie; Hu, Ming; Yang, Xu‐Heng; Xiang, Jian‐Nan; Li, Jin‐Heng
Abstract: A new, metal‐free method for the formation of C(sp 3 )–O bonds was established by PhI(OAc)2 ‐mediated oxygenation of benzylic C(sp 3 )–H bonds with N ‐hydroxyamides at room temperature, in which the C(sp 3 )–H oxidation is activated by a polyflurophenylamide group. Abstract : A metal‐free, room temperature route to construct C(sp 3 )–O bonds is described by PhI(OAc)2 ‐mediated oxygenation of a benzylic C(sp 3 )–H bond with the O–H bond in N ‐hydroxyamides. This method is facilitated by an electron‐withdrawing amide group, and provides a transition‐metal‐free room temperature alternative for the formation of C(sp 3 )–O bonds with highly functional group compatibility.